2007
DOI: 10.1101/gr.6522707
|View full text |Cite
|
Sign up to set email alerts
|

Architectures of somatic genomic rearrangement in human cancer amplicons at sequence-level resolution

Abstract: For decades, cytogenetic studies have demonstrated that somatically acquired structural rearrangements of the genome are a common feature of most classes of human cancer. However, the characteristics of these rearrangements at sequence-level resolution have thus far been subject to very limited description. One process that is dependent upon somatic genome rearrangement is gene amplification, a mechanism often exploited by cancer cells to increase copy number and hence expression of dominantly acting cancer ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
3
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(197 citation statements)
references
References 37 publications
12
177
3
2
Order By: Relevance
“…They invoke the rescue of individual stalled replication forks by switching the template during strand synthesis or resynthesis to an unrelated template that has only a few base pairs of homology. This results in joining of a strand to an unrelated sequence; it explains the insertion of genomic shards (small fragments of genome from elsewhere in the genome) (Bignell et al 2007), which are often found in the junctions, and are presumed to be the result of abortive attempts to use another template (Hastings et al 2009b); and it specifies that junctions show microhomology between the joined sequences of typically 2 to 5 bp. Our translocations were consistent with this pattern, showing microhomology of 1 to 8 bp at the junctions, and, in two cases, typical genomic shards (Supplemental Table 3).…”
Section: How Does This Model Relate To Existing Models Of Translocation?mentioning
confidence: 99%
See 2 more Smart Citations
“…They invoke the rescue of individual stalled replication forks by switching the template during strand synthesis or resynthesis to an unrelated template that has only a few base pairs of homology. This results in joining of a strand to an unrelated sequence; it explains the insertion of genomic shards (small fragments of genome from elsewhere in the genome) (Bignell et al 2007), which are often found in the junctions, and are presumed to be the result of abortive attempts to use another template (Hastings et al 2009b); and it specifies that junctions show microhomology between the joined sequences of typically 2 to 5 bp. Our translocations were consistent with this pattern, showing microhomology of 1 to 8 bp at the junctions, and, in two cases, typical genomic shards (Supplemental Table 3).…”
Section: How Does This Model Relate To Existing Models Of Translocation?mentioning
confidence: 99%
“…2B; Howarth et al 2008). The cloned junctions were at 10,438,664 bp and 9,108,545 bp (Table 1 Table 3), 80 kb away from the breakpoint, typical of the small fragments of distant sequence that are often found inserted in junctions, named ''genomic shards'' (Bignell et al 2007;Hastings et al 2009a). The resulting loss was clear in the SNP6 array-CGH data from Bignell et al (2010) (Supplemental Fig.…”
Section: Origin Of Duplicated Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial applications of these approaches have been quite successful (Bignell et al, 2007;Campbell et al, 2008). For example, Campbell et al (2008) used Illumina GA technology to attain the precise sequence of several hundred variants, comprising germline and somatic intra-and inter-chromosomal rearrangements in two lung cancer cell lines.…”
Section: Cancer Genome Rearrangements -An Impor-tant Component Of Thementioning
confidence: 99%
“…Next-generation sequencing technologies that allow the entire genomes of tumour cells to be sequenced will be particularly valuable for discovering fusion genes and other structural rearrange ments. The promise of this approach is illustrated by the remarkable structural complexity found in cancer genomes by using endsequence profiling 23 , genomic-region sequencing 24 or genome-wide parallel paired-end sequencing 25 (Box 1).…”
Section: Epigenomic Analysismentioning
confidence: 99%